2018
DOI: 10.1074/jbc.ra118.002698
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to oxygen: 3-Hydroxyanthrinilate 3,4-dioxygenase employs loop dynamics to accommodate two substrates with disparate polarities

Abstract: 3-Hydroxyanthranilate 3,4-dioxygenase (HAO) is an iron-dependent protein that activates O and inserts both oxygen atoms into 3-hydroxyanthranilate (3-HAA). An intriguing question is how HAO can rapidly bind O, even though local O concentrations and diffusion rates are relatively low. Here, a close inspection of the HAO structures revealed that substrate- and inhibitor-bound structures exhibit a closed conformation with three hydrophobic loop regions moving toward the catalytic iron center, whereas the ligand-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Our success in obtaining seven intermediate crystal structures provided an outstanding opportunity to address such a question in an iron-based dioxygenase. Previously, we have shown that the closed conformation due to 3-HAA binding increases the hydrophobicity of the iron center and causes a substantial increase of the O 2 affinity of the active site (16). The structural studies in this work show how the dioxygenase modulates the active-site conformation throughout the catalytic reaction.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…Our success in obtaining seven intermediate crystal structures provided an outstanding opportunity to address such a question in an iron-based dioxygenase. Previously, we have shown that the closed conformation due to 3-HAA binding increases the hydrophobicity of the iron center and causes a substantial increase of the O 2 affinity of the active site (16). The structural studies in this work show how the dioxygenase modulates the active-site conformation throughout the catalytic reaction.…”
Section: Discussionsupporting
confidence: 50%
“…The bond distance between Fe II and C3-hydroxyl group is 2.3 Å, while the C2-amino group is 3.2 Å from the Fe II ion (SI Appendix, Table S2). The previously observed loop movements that enhance the hydrophobicity of the Fe center and facilitate O 2 binding upon bidentate chelation of the substrate are not observed in this intermediate (16). Only one of three loops composed of residues 139 to 148 partially shift to the previously defined "closed" form (Fig.…”
Section: Hao Is Catalytically Active In the Crystalline State With Simentioning
confidence: 52%
See 3 more Smart Citations